Randomised controlled trial comparing the impact of supplementary feeding with either ready-to-use therapeutic food or corn-soy blend among malnourished anti-retroviral therapy clients in Malawi - Ndekha, MacDonald Joseph (My University, 2014)
Objectives: To investigate the effect of two different food supplements on body mass index (BMI) and fat-free body mass in wasted HIV-infected Malawian adults commencing highly active antiretroviral therapy (ART). Design: Randomised controlled, investigator blinded, clinical trial. Setting: Large, public ART clinic in a referral hospital in Blantyre, Malawi. Participants: 491 adults (>18 years) initiating ART with a body mass index (BMI) <18.5. Interventions: After screening for study-eligibility, consenting new ART registrants were randomised to receive either ready-to-use therapeutic food (RUTF) (n=245), or corn-soy blend (CSB) (n=246) supplements. Main outcome measures: The primary outcomes were changes in BMI and fat-free body mass following completion of an initial 3.5-month of both ART and supplementary feeding, and subsequently after 9.5 months of ART alone once supplementary feeding had stopped. Secondary outcomes were survival, hospitalisations, changes in health-related quality of life (HRQoL) assessment scores at 3.5, 6.5, 9.5 and 12.5 months, improvements from baseline in CD4 count, serum albumin, haemoglobin and HIV RNA viral load at 3.5 months, and adherence to ART. Results: A total of 1,343 new ART registrants during the study period were screened for study eligibility, from which some 511 individuals were study-eligible. Of these, 491 individuals (96%) were enrolled, 245 and 246 in the RUTF and CSB cohorts, respectively, with a mean BMI of 16.5 kg/m2. Following the 3.5-month supplementary feeding, study participants in the RUTF group had a significantly greater increase in BMI (2.1 [SD 1.8]) v 1.6 [SD 1.6] kg/m2, mean difference 0.50, 95% CI 0.10 to 0.80; p<0.01), and fat-free body mass (2.9 [SD 3.2] v 2.2 [SD 3.0] kg, mean difference 0.70, 95% CI 0.20 to 1.20; p< 0.01) compared to participants in the CSB cohort. No significant differences in CD4 count, HIV viral load, HRQoL measurements or ART adherence were noted between the two cohorts. Mortality was high and similar in both cohorts (27% v 26% in the RUTF and CSB cohorts, respectively). Multivariate Cox hazard modelling identified male gender (HR 1.75, 95% CI 1.32 to 2.31), lack of access to cotrimoxazole prophylaxis (CTX) (HR 2.4, 95% CI 1.3 to 4.7), severe wasting (BMI <16.0) at baseline (hazard ratio [HR] 10.3, 95% confidence interval [CI] 1.3 to 79.7), lower lean body mass (% body composition) (HR 10.3, 95% CI 1.2 to 86.8) at baseline and weight gain ≥ 10% of the initial body weight at 1.5-month study follow-up (HR 3.9, 95% CI 1.8 to 8.4), as factors significantly associated with high “early” (3.5-month) mortality. Trial retention rate on completion of the 3.5-month feeding intervention was 162/245 (66.1%) and 174/246 (70.7%) in the RUTF and CSB cohorts, respectively. Both groups continued with ART only thereafter. Nine and half months after the feeding intervention stopped, both cohorts had a similar BMI and fat-free body mass. Additionally, health-related quality of life, ART adherence, hospitalisations and mortality were similar between the two cohorts. Cox hazard modelling identified a lower lean body mass (% body composition) (HR 130, 95% CI 6.3 to 2699), a CD4 count of 50-199 (HR 3.7, 95% CI 1.2 to 11.1) and a CD4 count <50 (HR 11.9, 95% CI 2.1 to 65.2) at 3.5-month follow-up as factors significantly associated with post-supplementary feeding ART mortality. Conclusions: Supplementary feeding with RUTF resulted in a greater increase in BMI and fat-free body mass compared to feeding with CSB while study participants were receiving the food supplements. Although feeding with RUTF can ameliorate an established risk factor for xi mortality in HIV infection- BMI - the benefit is maintained only during the supplementary feeding period, and there was no evidence that this conferred any other benefits to study participants as they continued with ART. Targeted feeding of wasted ART patients for a period longer than 3 months, or pre-ART supplementary feeding of wasted patients to improve their BMI, merits future research.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Health Sciences, 2013.